A rapid review of periviable (22 + 0 to 23 + 6 weeks) counselling practices and the need for a trauma-informed care approach - Peterson, J.; Graham, C.; Johnstone, E. D.; Mahaveer, A.; Smith, D. M. (Frontiers in Pediatrics, 2025)
Given the risks of mortality and morbidity for infants born in the periviable period, a decision is made between parents and professionals prior to the birth as to whether survival-focused or comfort care is most appropriate at delivery. Medical information should be shared with parents and parental perspectives and priorities in relation to this information should be explored and integrated into the decision-making process. Conducting these conversations is complex and nuanced. This rapid review conducted a systematic search of the available literature relating to the approaches to and content of the pre-birth periviable conversation and identified three core themes: Transparency, Collaboration and Empowerment. In brief, these themes demonstrate that the information provided to parents should consistently outline all available care options relevant to their baby, including compassionately delivered, but honest and descriptive accounts of emotive options, such as comfort care. Information should be individualised to the specific circumstances and risk factors of that individual family. Perinatal professionals should seek to incorporate discussion of topics key to the ‘good parent belief’ to empower parents within their role. Avoiding or omitting discussion of uncertainty and dismissal of hope within these conversations was associated with parental distrust and impaired communication. The themes identified within this rapid review align with the principles of trauma-informed care and provide a structure for further research and service development focused on improving the quality and experience of pre-birth periviable conversations for future parents.Systematic Review Registration: https://www.crd.york.ac.uk/PROSPERO/view/CRD42022300099, PROSPERO identifier CRD4202230009.